The Story of an Operetta Le dernier sorcier by Pauline Viardot and Ivan Turgenev, Vol. 1 - Žekulin, Nicholas G. (Vortraege und Abhandlungen zur Slavistik, 1989)
Few readers of the works of the Russian author Ivan Turgenev are aware of the fact that he occasionally engaged in the writing of libretti. Even fewer people realize that Turgenev was interested in libretti-both theoretically and in practice- for much of his literary career. No attempt has yet been made to study his libretti in their essential context, that of Pauline Viardot׳s music. The present two-part study represent an effort at considering this apect of his life and work. It is based primarily on le Dernier Sorcier [The Last Sorcerer], arguably the best and most important of the Turgenev-Viardot operettas.